2018
DOI: 10.1038/s41598-018-27681-x
|View full text |Cite
|
Sign up to set email alerts
|

Host genotype-specific microbiota do not influence the susceptibility of D. magna to a bacterial pathogen

Abstract: Host-associated microbiota have been claimed to play a role in hosts’ responses to parasitic infections, often protecting the hosts from infection. We tested for such a role in the crustacean Daphnia and the parasitic bacterium Pasteuria ramosa, a widely used model system for host-parasite interactions. We first determined the infection phenotype (i.e., resistotype) of eight clonal D. magna genotypes against four strains of P. ramosa by attachment test, followed by 16 S rDNA amplicon sequencing to determine if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 54 publications
4
29
0
Order By: Relevance
“…They also serve as a bioindicator species for ecosystem health and, thus, are an important focus for research on the ecological impacts of global climate change. Research has shown that, as with other study systems, changes to microbial communities affect Daphnia fitness [5,6,26,40,41]. There is evidence from other systems that host genotype and environmental conditions may have an interactive effect on host microbiomes [1,7], and a recent study in D. magna provided the first report of such dynamics in this species [44].…”
Section: Introductionmentioning
confidence: 77%
“…They also serve as a bioindicator species for ecosystem health and, thus, are an important focus for research on the ecological impacts of global climate change. Research has shown that, as with other study systems, changes to microbial communities affect Daphnia fitness [5,6,26,40,41]. There is evidence from other systems that host genotype and environmental conditions may have an interactive effect on host microbiomes [1,7], and a recent study in D. magna provided the first report of such dynamics in this species [44].…”
Section: Introductionmentioning
confidence: 77%
“…This also speaks for functional redundancy although additional studies would be required to show this. At the genus level, only Bosea and Galbitalea had significantly positive association with Daphnia growth and fecundity, whereas the association for Leadbetterella and Hydrogenophaga, which are commonly found in Daphnia [63], was negative. The Bradyrhizobiaceae (Bosea) and Microbacteriaceae (Galbitalea) are bio-degraders capable of producing hydrolytic enzymes such as chitinase, cellulase, glucanase, protease, etc.…”
Section: Microbiome-fitness Relationshipsmentioning
confidence: 85%
“…; Sison‐Mangus et al. ). Such symbionts are facultative and experience a free‐living stage between hosts, making survival in both their host and external environment paramount.…”
mentioning
confidence: 99%
“…The influence of these factors on the success of colonization also depends upon the route of microbe transmission between hosts (Bright and Bulgheresi 2010). Where symbionts are environmentally acquired, abiotic factors can serve as the primary driving force behind microbial colonization (Thursz et al 1999;Sison-Mangus et al 2018). Such symbionts are facultative and experience a free-living stage between hosts, making survival in both their host and external environment paramount.…”
mentioning
confidence: 99%